Contextualizing Health and Aging in the Americas Effects of Space, Time and Place - Vega, William A.; Angel, Jacqueline L.; Gutiérrez Robledo, Luis Miguel F.; Markides, Kyriakos S. (Springer International Publishing : Imprint: Springer, 2019)
This book presents new insights into the consequences of the impending growth in and impact of the older segment of aging communities on local economies. It uses a comparative research framework to further our understanding of issues in health and aging in the transnational context of the health and migratory experience of the U.S.- Mexican population. It also provides an important contribution to the interdisciplinary investigation of new conceptual and methodological approaches in comparative studies (inter-group comparisons) of Hispanic aging and health research. Specifically, the chapters employ different methodologies to address issues related to immigration processes, family and household structure, macroeconomic changes in the quality of community life, and focus on the new realities of aging in Latino families in local communities. The book focuses on measurement, data-quality issues, new conceptual modeling techniques, and longitudinal survey capabilities. As such it is of interest to researchers and policy makers in social sciences and public health.